Emerging feline vector-borne pathogens in Italy - Giulia Morganti; Fabrizia Veronesi; Valentina Stefanetti; Trentina Di Muccio; Eleonora Fiorentino; Manuela Diaferia; Azzurra Santoro; Fabrizio Passamonti; Marina Gramiccia (Parasites & Vectors, 2019)
Abstract Background The epidemiology of feline vector-borne pathogens (FeVBPs) has been less investigated in cats than in dogs. The present study assessed the prevalence of Rickettsia spp., Babesia spp., Cytauxzoon spp. and Leishmania infantum infections in cat populations living in central Italy, by molecular and serological tools. Results A total of 286 healthy cats were randomly selected from catteries and colonies in central Italy. Peripheral blood and conjunctival swab (CS) samples were collected during surgical procedures for regional neutering projects. Sera were analysed by IFAT to detect anti-Rickettsia felis, R. conorii, Babesia microti and Leishmania IgG antibodies using commercial and home-made antigens. DNA extracted from buffy coats (BCs) was tested for Rickettsia spp., and Piroplasmida species, including Cytauxzoon spp. and Babesia spp. by PCR. Buffy coats and CS samples were assayed by a nested (n)-PCR for Leishmania spp. Sixty-two cats (21.67%) were seropositive to at least one of the tested pathogens. The serological assay revealed 23 (8.04%) and 18 (6.29%) positive cats for R. felis and R. conorii, respectively, with low titers (1/64–1/128). No antibodies against B. microti were detected. Neither Rickettsia nor Piroplasmida DNA were amplified using the specific PCR assays. Thirty-one cats (10.83%) tested positive to anti-Leishmania IgG, with titers ranging from 1:40 to 1:160 and 45 animals (15.73%) tested positive to Leishmania CS n-PCR, whereas none of the animals tested positive to BC n-PCR. Considering the results obtained by IFAT and CS n-PCR, a moderate agreement between the two tests was detected (κ = 0.27). Conclusions The results of the serological and molecular surveys showed a moderate exposure to Leishmania in the investigated cats and highlighted the limited molecular diagnostic value of BC versus CS samples for this pathogen. Conversely no evidence supported the circulation of Cytauxzoon spp. in domestic cats, in contrast with previous detections in European wild cats in the same areas monitored. The low positive titres for R. felis in association with no DNA BC amplification prevent speculation on the exposure of feline populations to this FeVBP due to the cross-reactivity existing within spotted fever group rickettsiosis (SFGR).